Between Mimesis and Fiction: Recognition in Adam Smith - Anzalone, Mariafilomena (Itinerari, 2023)
In Adam Smith’s ethics of sympathy, recognition is closely linked to seeking approval and esteem from other social actors. In the light of the undoubtedly great importance granted by Smith to social approval a series of questions arise, such as: Does the search for recognition necessarily imply the adoption by the individual of mimetic behaviours which, by replicating what is socially shared, guarantee approval and esteem? And to what extent does mimesis require a capacity for fiction? In this regard, is it not the case that individual moral evaluations risk being reduced to the conformist reverberation of those of society? The aim of this essay is first of all to understand in which terms Smith, in his Theory of Moral Sentiments, understands the link between mimesis, fiction and recognition. To this end, the role played by mimesis and fiction will be scrutinised along the various interconnected dimensions that structure the complex phenomenon of recognition: the emotional, the one linked to public success, and the moral one. Finally, in the light of the peculiar account on mimesis developed by Smith on aesthetic grounds, also the ethical implications of this link will be discussed.